2022
DOI: 10.3390/foods11050737
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Substituted Sulfated Alfalfa Polysaccharides and Evaluation of Their Biological Activity

Abstract: Alfalfa polysaccharides (AP) receive wide attention in the field of medicine, because of their anti-inflammatory property. However, AP has high molecular weight and poor water solubility, resulting in low biological activity. We wanted to obtain highly bioactive alfalfa polysaccharides for further research. Herein, we successfully synthesized highly substituted sulfated alfalfa polysaccharides (SAP) via the chlorosulfonic acid (CSA)-pyridine (Pyr) method, which was optimized using response surface methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The active groups of glycans were closely related to their bioactivities. For example, the existence of sulphonic acid groups in alfalfa polysaccharide was beneficial for its biological activities, such as water solubility, antioxidant activity and anti‐obesity (Li et al ., 2022). Xu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active groups of glycans were closely related to their bioactivities. For example, the existence of sulphonic acid groups in alfalfa polysaccharide was beneficial for its biological activities, such as water solubility, antioxidant activity and anti‐obesity (Li et al ., 2022). Xu et al .…”
Section: Resultsmentioning
confidence: 99%
“…The active groups of glycans were closely related to their bioactivities. For example, the existence of sulphonic acid groups in alfalfa polysaccharide was beneficial for its biological activities, such as water solubility, antioxidant activity and anti-obesity (Li et al, 2022). Xu et al also found that the sulphated modification of the polysaccharide from Sphallerocarpus gracilis increased its antioxidant effects on DPPH, hydroxyl, superoxide radical scavenging and ferric-ion reducing (Xu et al, 2016).…”
Section: Active Groups Of Lzp1-lzp3mentioning
confidence: 99%
“…Therefore, to prepare sulfated derivatives with higher activity, orthogonal experiments, and response surface methodology (RSM) are usually used to optimize the preparation conditions of polysaccharides derivatives. [32][33][34] Nagpal et al [35] used CSA/Pyr reagent to synthesize sulfated derivatives of okra pectin with the DS ranging from 0.39 to 1.13, and optimized the reaction conditions via Box-Behnken Design (BBD) of RSM. The results show that the optimum reaction conditions of sulfated okra pectin were as follows: CSA/Pyr ratio of 0.28 and reaction time of 3.05 h. Compared with unmodified okra pectin, sulfated okra pectin has significantly enhanced anticoagulant and antimicrobial properties.…”
Section: Chlorosulfonic Acid Pyridine Methodsmentioning
confidence: 99%
“…The proportion of sulfation reagents, reaction time, and reaction temperature are the main factors that affect the DS. The appropriate test conditions are generally explored by orthogonal or response surface design to obtain the desired DS [ 20 , 21 ].…”
Section: Polysaccharide Modificationmentioning
confidence: 99%